Mechanization of Rock Drilling at Inco (7d43c0c3-5deb-410e-a951-bde518860ba9) - G. R. Green; R. C. McDonald (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1974)
The International Nickel Co., Ontario Div. mines, faced with rising production requirements, short labor supply, and ever increasing labor costs turned to mechanized mining for a solution to its problems. The degree of mechanization of ore removal has increased from 1966 with the purchase of the first diesel-powered load-haul-dump (LHD) machine to the present, with over 53% of all underground production handled by these units. Keeping pace with mechanized ore removal, there has been a parallel development of drilling equipment to complement the mucking units. This paper deals with the applications and economic advantages of mechanized drilling at the underground mines of Inco, Ontario Div. It covers the use of various types of mechanized drills in such mining methods as cut-and-fill, induced block caving, and sublevel caving. The economics of raise boring are also discussed.